Model Pemberdayaan Ekonomi Mustahiq Melalui Zakat - Achmad Syaiful Hidayat Anwar (Jurnal Ekonomi Akuntansi dan Manajemen, 2016)
The aim of this research is to test and completing the model of Mustahiq Economic Empowerment by Zakat Utilizing. The research activities consist of simulation and completing of model. Data collecting method that used were interview and focus group discussion with the mustahiq. Based on the analysis results can be conclude that mustahiq agree and support concern with the mustahiq empowerment model. Mustahiq expect by the implementation of empowerment model will be able to increase mustahiq’s welfare by main indicator is the canging of social status from mustahiq to muzakki. In addition, mustahiq suggest a partnership program between BAZ and LAZ management, government, and entrepreneurs for training dan education concern with business management. Key Words: Empowerment, Economic, Mustahiq, Zakat